Caracterização térmica e físico-química do sistema argila-8-hidroxiquinolina na remoção de íons Fe(III), Ni(II) e Co(II) - Franzin, Bruno Trevizan [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Anthropogenic activities and the increase in population lead to environmental damage, mainly in water sources, which has been receiving dumps containing potentially toxic and non-biodegradable poluentex, among them the metal ions, problems on which the present study is inserted. For both assessed the behavior of binary system clay-8-hydroxyquinoline in aqueous suspension and in the solid state, in the absence and presence of metallic ions, Fe(III), Ni(II) and Co(II). In aqueous suspension systems were evaluated by Uv-Vis, indicating ternary complex species formation (clay-8-hydroxyquinoline-Mn+) of greater stability when compared to the absence of clay, complex formed between the organic complexing and the ions Mn+. The Uv-vis results suggest order of stability of complexes formed being Fe(III)>Ni(II)>Co(II). The composites in the solid state were assessed using XRD techniques, TG/DTG-DTA and SEM. The images obtained by SEM, as well as the x-ray diffractometry corroborate in the elucidation of formation of the ternary complex of the type species {[Si-O-]x-[Mn+-(8-HQ)k}+n-x-k; in which this last technique we observed increase in basal distance of clay in the presence of ions studied. The thermal study complemented the idea of complex species formation, showing stages of decomposition similar and confirming the greater thermal stability of the complex in the presence of Fe(III) consecutive by Ni(II) and Co (II). Adsorptive study on adsorbato is ion Fe (III) and Ni(II) and the adsorbents are composite and pure clay, the largest adsorption was observed for Ni(II) ions, compared to Fe(III), but the latter, there was an increase in the percentage adsorbed when employed the composite, which contributes to higher proposal idea complex stability, clay-8-HQ-Fe(III). According to the described it is possible to infer the sensitivity of composite for the ions studied, with possibility of application on removal...

As atividades antrópicas e o aumento populacional acarretam danos ao ambiente, principalmente nas fontes de águas, que vem recebendo despejos contendo poluentex potencialmente tóxicos e não biodegradáveis, entre eles os íons metálicos, problemática na qual o presente estudo está inserido. Para tanto avaliou-se o comportamento do sistema binário argila-8-hidroxiquinolina em suspensão aquosa e em estado sólido, na ausência e presença dos íons metálicos, Fe(III), Ni(II) e Co(II). Os sistemas em suspensão aquosa foram avaliados por espectrofotometria, indicando formação de espécie ternária complexa (argila-8-hidroxiquinolina-Mn+) de maior estabilidade quando comparado com sistema na ausência da argila, cujo complexo formado entre o complexante orgânico e os íons Mn+. Os resultados de Uv-vis sugerem ordem de estabilidade dos complexos formados sendo Fe(III)>Ni(II)>Co(II). Os compósitos em estado sólido foram avaliados empregando técnicas de XRD, TG/DTG-DTA e MEV. As imagens obtidas por MEV, bem como a difratometria de raio X corroboram na elucidação de formação da espécie ternária complexa do tipo {[Si-O-]x - [Mn+-(8-HQ)k}+n-x-k; no qual nesta ultima técnica observou-se aumento no espaçamento basal da argila na presença dos íons estudados. O estudo térmico permite elucidar a formação de espécie complexa, apresentando etapas de decomposição semelhantes e confirmando a maior estabilidade térmica do complexo na presença de Fe(III) seguido de Ni(II) e Co(II). No estudo adsortivo tomando como adsorbato íons Fe(III) e Ni(II) e como adsorvente o compósito e a argila pura, a maior adsorção foi observada para íons Ni(II), comparado a Fe(III). Porém observou-se que para o Fe(III), houve aumento na porcentagem adsorvida quando empregado o compósito, o que contribui para a proposta de maior estabilidade do complexo, argila-8-HQ-Fe(III). De acordo com o verificado neste estudo é possível inferir a...
Keywords: Quimica; Eletroquimica; Argila; Montmorilonita